凍土環境利用と保全に向けた凍土荒廃影響評価の共創 - 飯島, 慈裕; Iijima, Yoshihiro; 高倉, 浩樹; Takakura, Hiroki; 齋藤, 仁; Saito, Hitoshi; 檜山, 哲哉; Hiyama, Tetsuya; 岩花, 剛; Iwahana, Go; 桐村, 喬; Kirimura, Takashi (三重大学, 2023)
application/pdf 本研究は、シベリアでの複合リモートセンシング解析から、実際の凍土融解地形の発達程度や空間密度と地形沈降・地表面状態変化との対応関係を明らかにするとともに、過去に人為的撹乱があった地域で顕著な荒廃が進行していることを明らかにした。モンゴルでは、永久凍土の消失の可能性のある山岳域周辺に おいて、湧水の質的変化を明らかにし、凍土荒廃に伴う水資源枯渇の危険性を示した。凍土荒廃の社会影響について、東シベリアでの社会統計データの地理情報解析から、先住民の拠点となっている集落を中心として人口増加と住宅地の拡大が進み、凍土荒廃地域と土地開発がさらに近接する傾向が示された。 Based on combined remote sensing analyses in Siberia, this study clarified the correspondence between the actual degree of development and spatial density of permafrost thaw landforms and changes in topographic subsidence and land surface conditions. It revealed that significant degradation has progressed in areas that have been subject to anthropogenic disturbance in the past. In Mongolia, we clarified the qualitative changes of spring water around mountainous areas where permafrost disappearance may occur and showed the danger of water resource scarcity associated with permafrost degradation. Regarding the social impact of permafrost degradation, geographic information analysis of socio-demographic data in Eastern Siberia showed that population growth and expansion of residential areas centered on settlements that serve as centers for indigenous peoples and a tendency for land development to move even closer to permafrost degradation areas. 2019年度～2022年度科学研究費補助金(基盤研究(A))研究成果報告書 19H00556 research report